2022
DOI: 10.1002/pld3.430
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome DNA methylation patterns of Oryza sativa (L.) and Oryza glumaepatula (Steud) genotypes associated with aluminum response

Abstract: Epigenetic mechanisms in crops have emerged as a fundamental factor in plant adaptation and acclimation to biotic and abiotic stresses. Among described epigenetic mechanisms, DNA methylation has been defined as the most studied epigenetic modification involved in several developmental processes. It has been shown that contrasting methylation marks are associated with gene expression variations between cultivated and wild crop species. In this study, we analyzed single‐base resolution methylome maps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…This is a consequence of low CHH methylation near the centromere region and greater presence in the chromosome arms. Gallo-Franco et al [ 27 ] reported high CHH methylation levels of transposable elements close to genes in rice, which supports the conclusion of Martin et al [ 28 ] for grass species that long genes and genes close to transposable elements tend to have CHH islands more frequently. It could be hypothesized that the presence of these CHH islands is promoting the positive correlation between methylation and recombination in gene-rich regions.…”
Section: Resultssupporting
confidence: 64%
“…This is a consequence of low CHH methylation near the centromere region and greater presence in the chromosome arms. Gallo-Franco et al [ 27 ] reported high CHH methylation levels of transposable elements close to genes in rice, which supports the conclusion of Martin et al [ 28 ] for grass species that long genes and genes close to transposable elements tend to have CHH islands more frequently. It could be hypothesized that the presence of these CHH islands is promoting the positive correlation between methylation and recombination in gene-rich regions.…”
Section: Resultssupporting
confidence: 64%
“…CHH was the context with least negative correlation of genes to methylation for Acer. Less correlation of methylation with genes means more intersection in TE filled intergenic space, lending support to the hypothesis that in some species, the balance of CHH methylation, TE suppression, TE proximity to genes, and gene body methylation could indicate complex strategies playing a role regulating key genes at TE boundary regions, as observed in grasses(Martin et al, 2021) and Oryza(Gallo-Franco et al, 2022).…”
supporting
confidence: 64%
“…Gallo‐Franco et al. ( 2022 ) found that aluminum tolerant and susceptible varieties of O. sativa and Oryza glumaepatula each had unique differentially methylated regions, and each species was associated with different TEs potentially affecting regulation of these regions. While relationships between environmental stress, methylation, and increased proximal TE activity have been observed in numerous studies, this regulation is complex and potentially involves specific methylation mechanisms, such as the Copia ONSEN in both Arabidopsis and Oryza .…”
Section: Resultsmentioning
confidence: 99%
“…In rice, a genome-wide methylation comparison between cultivated ( Oryza sativa ) and the more Al tolerant wild species ( O. glumaepatula ) was undertaken ( Gallo-Franco et al., 2022 ). In the case of O. sativa , 4633 differentially methylated regions (DMRs) were observed - 38% showed increased methylation and 62% were hypomethylated.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Lastly, DNA as well as RNA methylation leads to the regulation of the expression of stress signalling and defense associated genes. The WGBS analysis revealed thousands of differentially methylated regions in plants in response to Cd, Pb, Al and Hg treatment ( Cong et al., 2021 , Feng et al., 2016 ; Gallo-Franco et al., 2022 ; Tang et al., 2023 ). In rice, the majority (nearly 70%) of Cd responsive genes were also differentially methylated.…”
Section: The Relation Of Epigenetic and Epitranscriptomic Changes To ...mentioning
confidence: 99%